2011
DOI: 10.1038/aja.2011.42
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of the surgical treatment of Peyronie's disease with Egydio's technique: a European multicentre study

Abstract: The long-term outcomes of 157 patients affected by Peyronie's disease (PD) who underwent penile straightening with Egydio's technique between January 2004 and December 2008 are reported. Only patients with PD who were stable for at least 6-12 months prior to surgery were enrolled in this study. Preoperative assessment included a dynamic echo colour Doppler ultrasound scan to evaluate the degree of penile deformity and the peak systolic velocity in the cavernosal arteries and an assessment of erectile function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
57
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 27 publications
0
57
0
2
Order By: Relevance
“…The Egydio technique, which consists of plaque incision and grafting according to geometrical principles, is a valid and highly effective surgical approach for the correction of penile deviations. Recently, a European multicentre study showed that the procedure is a safe and easily reproducible technique for the correction of penile curvature, with excellent cosmetic and functional results [15]. Nevertheless, it must be kept in mind that PD correlates with severe ED; therefore, straightening operations in such cases may not provide the desired benefit, as inadequate rigidity may persist and impede sexual intercourse.…”
Section: Discussionmentioning
confidence: 99%
“…The Egydio technique, which consists of plaque incision and grafting according to geometrical principles, is a valid and highly effective surgical approach for the correction of penile deviations. Recently, a European multicentre study showed that the procedure is a safe and easily reproducible technique for the correction of penile curvature, with excellent cosmetic and functional results [15]. Nevertheless, it must be kept in mind that PD correlates with severe ED; therefore, straightening operations in such cases may not provide the desired benefit, as inadequate rigidity may persist and impede sexual intercourse.…”
Section: Discussionmentioning
confidence: 99%
“…In up to 46% of patients, adequate straightening is not achieved with grafting alone. In these patients, further straightening should be achieved by plicating the tunica albuginea on the side opposite to the incision rather than by performing additional incisions and grafting, as this is likely to further impair the quality of the erections [44–56].…”
Section: Surgical Approachesmentioning
confidence: 99%
“…There are three broad categories of TA plaque incision (double-Y, H-shaped, and Egydio geometric) that are made at the point/relative to the maximum curvature on the convex side of the penis, followed by placement of a graft material(autologous, allografts, xenografts, and synthetic) to repair the defect and potentially lengthen the shorter side of the penis. 1,3,[69][70][71][72]76,78,[86][87][88][89][90][91][92][93][94][95][96][97][98][99][100][101] There is a strong trend towards minimal TA disruption, therefore favoring incision or partial excision techniques;…”
Section: Grafting Proceduresmentioning
confidence: 99%